2015
DOI: 10.1177/1606822x15602606
|View full text |Cite
|
Sign up to set email alerts
|

Markedness and Lexical Typicality in Mandarin Acceptability Judgments

Abstract: It has long been known that native speakers judge nonlexical forms as more acceptable the more lexically typical they are (i.e., similar to real words). It has also been shown that speakers judge less marked (i.e., universally more natural) structures as more acceptable than more marked structures. In this study, we investigate for the first time how markedness and lexical typicality interact, using data from a large corpus of experimentally collected Mandarin native-speaker judgments of nonlexical syllables. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In their investigation of lexical neighbours, however, cases with both a segmental difference and a tonal difference were not included, so it is not possible to establish the relative contribution of segments and tones in determining lexical neighbours in Mandarin. Myers (2015) considers segmental phonotactics without tone in Mandarin, focusing on a comparison of the effect of lexical typicality and typological frequency on acceptability judgements. Lexical typicality is defined on the basis of how many lexical syllables in Mandarin share an item's onset consonant, and typological frequency in terms of the number of phoneme inventories that exhibit this consonant across languages.…”
Section: Introductionmentioning
confidence: 99%
“…In their investigation of lexical neighbours, however, cases with both a segmental difference and a tonal difference were not included, so it is not possible to establish the relative contribution of segments and tones in determining lexical neighbours in Mandarin. Myers (2015) considers segmental phonotactics without tone in Mandarin, focusing on a comparison of the effect of lexical typicality and typological frequency on acceptability judgements. Lexical typicality is defined on the basis of how many lexical syllables in Mandarin share an item's onset consonant, and typological frequency in terms of the number of phoneme inventories that exhibit this consonant across languages.…”
Section: Introductionmentioning
confidence: 99%
“…On the T3-T4 continua, regardless of lexicality, the most frequent T4 was favored over the most marked T3. At the segmental level, markedness has been shown to affect speakers' word acceptance to different degrees based on how wordlike it is (Myers and Tsay, 2005;Myers, 2015). Myers (2015) collected word acceptance judgments from 114 Mandarin speakers who were presented with 3,274 monosyllabic non-words and asked to judge if the stimulus they heard was "like Mandarin" or was "not like Mandarin."…”
Section: Discussionmentioning
confidence: 99%
“…Word acceptability judgments can also be affected by markedness (Zuraw, 2000(Zuraw, , 2002Frisch et al, 2004;Jin and Lu, 2019). For example, Myers (2015) showed that Mandarin syllables with more marked onsets were more likely to be accepted as words than those with less marked onsets by Mandarin speakers. However, the effects of frequency and markedness on perceptual categorization is less clear, especially at the suprasegmental level.…”
Section: Introductionmentioning
confidence: 99%
“…The answer to this question seems to depend on the task. In general, listeners seem to prioritize the use of lexical knowledge, relying on their phonotactic knowledge only when lexical activation fails (Shademan, 2006;Vitevitch & Luce, 1999; although see Myers, 2015, and related works showing significant contributions of neighborhood density on wordlikeness judgments in non-English languages). Additionally, Mattys, White, and Melhorn (2005) investigated whether participants pay more attention to lexical or sublexical (segmental and prosodic) segmentation cues when they are in conflict.…”
Section: Effects Of Phonotactic Knowledge On Speech Perceptionmentioning
confidence: 99%